Handgun Carrying Among Youth in the United States: an Analysis of Subtypes - Vaughn, Michael G. (Youth violence and juvenile justice, 2017)
Despite a wealth of research finding that adolescents who carry handguns are involved in risky behaviors, there has been little exploration into the heterogeneity of this behavior. Using a pooled sample of 12- to 17-year-olds from the National Study on Drug Use and Health who report past-year handgun carrying (N = 7,872), this study identified four subgroups of handgun carriers: low risk (n = 3,831; 47.93%), alcohol and marijuana users (n = 1,591; 20.16%), fighters (n = 1,430; 19.40%), and severe externalizers (n = 1,020, 12.51%). These subgroups differed on demographic, behavioral, and psychosocial characteristics. Findings are discussed in light of prevention and focused deterrence.